After Christendom? how the church is to behave if freedom, justice and a Christian nation are bad ideas - Hauerwas, Stanley, 1940- (Nashville, TN Lancer, 1991)
Includes bibiographical references and index.
Keywords: Church and the world; Christianity and culture; Christian ethics; Secularism; Christianity -- 20th century